Integrated Process Design and Economic Evaluation of Waste-to-Biomaterial Conversion: Hydroxyapatite Production from Blue Crab Shells using Aspen Plus - Nugroho, Aldi Nugroho; Gumelar, Tobing; Aska, Silma Elvaretta; Rizqiyah, Vita Fatichah; Kamilah, Villia Lidzati; Rosanti, Maharani Sugito; Venanto, Dimas Gilang; Ma'mun, Ummu Zahroh; Ramadhan, Haykal Nur Fajri; Ningrum, Eva Oktavia (IPTEK The Journal of Engineering, 2025)
The demand for bone transplant materials is rising in Indonesia. A biogenic calcium supply for hydroxyapatite (HAp), the primary inorganic component of human bone, is provided by blue crab shells, which are produced contain 53.70–78 weight percent CaCO₃. A steady-state method for producing HAp from crab shells is developed and assessed in this study, utilizing Aspen Plus V14 in conjunction with the Aspen Process Economic Analyzer. The simulated flowsheet comprises solid–liquid separation, drying/sintering, CaO storage, CaO hydration, HAp precipitation with H₃PO₄. The global thermodynamic model chosen is the SOLIDS property approach, and stoichiometric reactions with Arrhenius-type power-law kinetics are used to simulate HAp production. In the simulation, 150.246 kg·h⁻¹ HAp, or roughly 1451.81 t·year⁻¹, is predicted for a design base of 46.48 kg·h⁻¹ CaO. A 20-year equipment lifetime, 8000 operating hours annually, a 20% rate of return, and zero-cost shells are assumed in the economic study. This results in a total capital cost of USD 1.94 million and an annual operating cost of USD 1.31 million. The findings offer a quantifiable starting point for evaluating the technical viability of waste-to-HAp systems and directing additional experimental validation, life-cycle analysis, and process improvement.